2009
DOI: 10.1093/ejo/cjn127
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and tissue inhibitors of metalloproteinases in gingival crevicular fluid during orthodontic tooth movement

Abstract: Orthodontic tooth movement requires extensive re-modelling of the periodontium. Matrix metalloproteinases (MMPs) degrade the extracellular matrix during re-modelling, while their activity is regulated by the tissue inhibitors of metalloproteinases (TIMPs). The aim of this study was to investigate differences in MMP and TIMP levels in the gingival crevicular fluid (GCF) at the resorption and apposition sides of orthodontically moved teeth, and to compare these with control teeth. GCF samples were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 36 publications
6
49
0
Order By: Relevance
“…Abdul Wahab et al, 51 Perinetti et al, 76 Serra et al, 44 Alfaqeeh 49 Ingman et al, 3 Ribagin and Rashkova 25 MMP-9 Grant et al, 86 Bildt et al 83 TIMP-1, TIMP-2 Grant et al, 86 Bildt et al 83 Bone biomarkers OPG Rody et al, 57 Tuncer et al, 81 Grant et al, 86 Barbieri et al, 69 Kawasaki et al, 40 Toygar et al, 93 Nishijima et al 39 …”
Section: Ldhmentioning
confidence: 99%
“…Abdul Wahab et al, 51 Perinetti et al, 76 Serra et al, 44 Alfaqeeh 49 Ingman et al, 3 Ribagin and Rashkova 25 MMP-9 Grant et al, 86 Bildt et al 83 TIMP-1, TIMP-2 Grant et al, 86 Bildt et al 83 Bone biomarkers OPG Rody et al, 57 Tuncer et al, 81 Grant et al, 86 Barbieri et al, 69 Kawasaki et al, 40 Toygar et al, 93 Nishijima et al 39 …”
Section: Ldhmentioning
confidence: 99%
“…Gelatin zymography has also been used to detect active and latent MMPs in GCF samples collected after orthodontic movement. 24 Partially active MMP-1 was found in GCF in both tension and compression sites but was never detected in control teeth.…”
Section: Discussionmentioning
confidence: 95%
“…Our study examined treated periodontitis subjects under maintenance, while other authors [17][18][19]24 studied periodontally healthy individuals. However, using multiplex bead immunoassay we have also examined the effects of orthodontic forces on periodontally healthy teeth and found MMPs changes for the compression sites but not for the tension sites as a result of mechanical forces.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that after a regular orthodontic load osseous alveolar remodeling canÂŽt be based on a simple but generally accepted model that resorption it's caused by compression and bone formation by tension. Bildt et al (2009) taking into account that Matrix metalloproteinases (MMPs) degrade the extracellular matrix during re-modelling, while their activity is regulated by the tissue inhibitors of metalloproteinases (TIMPs), made a study to find the differences in MMP and TIM levels in crevicular fluid corresponding to the bone resorption and apposition sides on orthodontically moved teeth and compare them to a control group. The sample was 8 patients with premolar extractionsapplying a 150 gf force to distalize the canine.…”
Section: But What It's a Light Force In Orthodontics?mentioning
confidence: 99%